WELFARE GAIN FROM CARBON TAX APPLIED TO LEISURE AIR TRAFFIC - Martín-Cejas, Roberto Rendeiro; del Pino, Francisco López (Journal of Tourism, Sustainability and Well-being, 2017)
The rapid growth in the air transport required satisfying the increased demand for tourism become a factor of unsustainability due to the substantial environmental impact that supports such a development. There is the need to establish an alternative to the traditional air transport pricing structure that reflects the true cost that air market operators impose on others. This paper analyses one application of a Carbon tax by considering the CO2 emission costs as a valuable input. A tentative tax on CO2 emissions from air transport is calculated considering its applications in leisure air transport market. Finally, one of the main conclusions of the analysis performed is that the available evidence suggests that international aviation emissions should be restricted. In this case, a Ramsey pricing structure, which involved aviation users bearing the environmental costs, would work reasonably well at restricting inefficient demand and produce a reasonable welfare gain respect to the do-nothing scenerywill be pointed out.